Karakteristik sensori, fisikokimia, dan mikrobiologi pada produk kolpie : pie dengan substitusi tepung ubi ungu dan isian vla kolak pisang - Adiwinata, Doni; Istiqomah, Zidna Amalia Al; Fitria, Aini Nur; Nurpitriani, Irna; Apriliani, Widya; Lazuardi, Amanda Deviena; Nurtiana, Winda (Faculty of Agriculture Science & Technology, 2025)
Kolpie is an innovative pie product made from a combination of purple sweet potato flour and wheat flour with a filling of kolak pisang custard, developed to enhance the value of local food through sensory evaluation and scientific analysis. Sensory tests were conducted on four different formulations with varying flour ratios, and the best formulation was determined to be F3 (70 g purple sweet potato flour: 190 g wheat flour), receiving the highest scores for taste, aroma, and texture. Physicochemical analysis of the selected formulation showed a moisture content of 37.04%, fat 20.53%, protein 2.99%, total sugar 85.38%, and starch 14.52%. The product exhibited a reddish color with low brightness due to the anthocyanin content in purple sweet potatoes. Meanwhile, the ash content was 1.33%, within the acceptable SNI limit. However, microbiological testing revealed a Total Plate Count (TPC) of 4.2 × 10? CFU/g, exceeding the maximum allowable SNI threshold (1 × 10? CFU/g), indicating potential contamination during production. Overall, Kolpie demonstrates promising potential as a local food product with high sensory and nutritional value, though improvements in microbial safety and filling stability are needed for commercial viability.